Large-Area Binary Blazed Grating Coupler between Nanophotonic Waveguide and LED. (13th July 2014) - Li, Hongqiang; Zhou, Wenqian; Zhang, Meiling; Liu, Yu; Zhang, Cheng; Li, Enbang; Miao, Changyun; Tang, Chunxiao
Abstract : A large-area binary blazed grating coupler for the arrayed waveguide grating (AWG) demodulation integrated microsystem on silicon-on-insulator (SOI) was designed for the first time. Through the coupler, light can be coupled into the SOI waveguide from the InP-based C-band LED for the AWG demodulation integrated microsystem to function. Both the length and width of the grating coupler are 360 μ m, as large as the InP-based C-band LED light emitting area in the system. The coupler was designed and optimized based on the finite difference time domain method. When the incident angle of the light source is 0 °, the coupling efficiency of the binary blazed grating is 40.92%, and the 3 dB bandwidth is 72 nm at a wavelength of 1550 nm.